1992
DOI: 10.1088/0953-8984/4/49/017
|View full text |Cite
|
Sign up to set email alerts
|

The site and local environment of Fe3+in LiNbO3investigated with ENDOR

Abstract: The superhyperflne (SHF) inleraclions of Fe'+ impurities with five shells o f Li neighbours were measured in B nearly stoichiometric LiNbOj clystal by applying eleclron nuclear double resonance (ENWR). Sirnilarty lo what was found for Li'BO,, lhe Sile of Fe'+ in LiNbO, has a threefold ymmely. The analysis of the ENDOR speclra clearly s h m that Fe'+ is on a subslilulional ti+ site. lhe varialions of shape and intensily of WWR lines belonging to specific ligand nuclei when rotating lhe clyslal in lhe Static mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…The analysis of the ENDOR spectra indicated that Fe3+ ions were at the Li+ sites in a nearly stoichiometric LiNbO, crystal [15]. The observed temperature variation [ l l ] of the ZFS parameter b: indicates that the Fe3+ ion moves towards the centre of the oxygen octahedron as the Nb5+ ion does.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the ENDOR spectra indicated that Fe3+ ions were at the Li+ sites in a nearly stoichiometric LiNbO, crystal [15]. The observed temperature variation [ l l ] of the ZFS parameter b: indicates that the Fe3+ ion moves towards the centre of the oxygen octahedron as the Nb5+ ion does.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental results are illustrated in Figure 4.2. ENDOR [34] and X-ray experiments [35] clearly indicate that the Fe centers occupy Li sites.…”
Section: Extrinsic Centersmentioning
confidence: 96%
“…Based on the above discussion, we deduce that the Fe 3+ ion in LiNbO 3 :Fe 3+ system may substitute for both Li + and Nb 5+ sites with different environment. In the experimental aspect, both the substitutional Li + and Nb 5+ sites have been, respectively, observed by Sothe et al's ENDOR experiment [34] and Yan et al ' s spectral emission experiment [7].…”
Section: Article In Pressmentioning
confidence: 99%